Pengaruh Persepsi Dukungan Organisasional, Komunikasi Organisasi dan Kemampuan Kerja terhadap Kinerja Aparatur Sipil Negara Melalui Motivasi - Jasmiati Paba; Wahyu Maulid Adha; Zainur Hidayah (Al-Buhuts, 2024)
The purpose of this study was to determine the effect of perceived organizational support, organizational communication, work ability and work motivation on ASN performance, the effect of organizational support, organizational communication, work ability and work motivation on ASN performance through work motivation. The research approach is quantitative, by taking samples of employees and extension workers at the BKKBN Representative Office of West Sulawesi Province. Data collection techniques by distributing questionnaires. Data analysis techniques using descriptive analysis and SmartPLS 3.2.9 analysis. The results of the study found that organizational support has a direct effect on ASN performance, Organizational communication has a direct effect on ASN performance, Work ability has a direct effect on ASN performance, Work motivation has a direct effect on ASN performance, because with high work motivation, ASN tends to work better and more focused, thus having an impact on improving work. Organizational support does not affect ASN performance through work motivation, so the indication in this study is that the perceived organizational support is not strong enough to encourage ASN to improve its performance through work motivation. Organizational communication affects ASN performance through work motivation, Work ability affects ASN performance through work motivation at the BKKBN Representative Office of West Sulawesi Province.